Sensitivities to neutrino non-standard interactions from the disappearance of muon (anti)neutrinos at the NOvA experiment - Prais, Luiz Ricardo (2020)
The experimental confirmation of the phenomenon of neutrino oscillations provided evidence for a non-zero value for the mass of neutrinos, a property not initially predicted by the Standard Model of Physics. Investigations of the existence of the so called Physics Beyond the Standard Model is a subject of growing interest and effort in the field of particle physics. Interactions of neutrinos with matter are well described by the Standard Model, however in the presence of new Physics, additional phenomena regarding neutrino properties would be possible, including non-standard interactions of neutrinos with matter. The NOvA experiment, at Fermilab, has been investigating neutrino oscillations through studies of νμ produced at the Fermilab accelerator facilities, and also comprise a suitable environment for investigation of additional phenomena taking part in the neutrino oscillation framework. We show in this thesis the results of the sensitivity studies to neutrino non-standard interactions in the NOvA experiment through investigation of the disappearance of muon (anti)neutrinos during their evolution in the NOvA 810 km baseline. We investigate the effect of the NSI parameters, |εεμτ|ε and δμτ, on the determination of the standard oscillation parameters sin2(θ23) and Δm2 32 , as well as the relation between each parameter, for both neutrino mass hierarchies. This study makes use of an exposure of 9.48 × 1020 POT for neutrino beam (FHC), and 12.33 × 1020 POT for antineutrino beam (RHC). No deviations from the standard oscillation scenario is found at the 90% CL limit. The joint neutrino and antineutrino fit yields a limit of |εεμτ|ε ≤ 0.086 (0.085) for a fixed value of δμτ = 0, and |εεμτ|ε ≤ 1.054 (1.053) for the case where both NSI parameters are fitted, for the normal (inverted) neutrino mass hierarchy, at the 90% CL. In the current sensitivity, all values of δμτ are found to be allowed. The 90% CL interval for the standard oscillation parameters are Δm2 32 ∈ [2.379, 2.580] and [2.379, 2.580] and sin2(θ23) ∈ [2.379, 2.580] and [0.420, 0.602] for the normal hierarchy scenario, and Δm2 32 ∈ [2.379, 2.580] and [−2.639, − 2.438] and sin2(θ23) ∈ [2.379, 2.580] and [0.418, 0.602] for the inverted hierarchy scenario.